Pengaruh Ekstrak Etanol Daun Mangkokan (Nothopanax scutellarium. Merr) Terhadap Fungsi Hati Dan Kadar Kreatinin Urin Mencit Putih Jantan - Helmi Arifin; Rahmi Yulia Nesia; Elisma Elisma (STIFARM Padang, 2011)
The effect of ethanolic extract of Nothopanax scutellarium. Merr on liver function and urine creatinine level of male white mices had been done. The extract was administered orally with variation of dose at 150, 300, 600 mg/kg BB one times a day for 15, 30, 45 days. As a control group was used male white mices that administered only Na CMC 0,5% solution. The result showed that administered of ethanolic extract Nothopanax scutellarium. Merr at variation of dose did not influence on liver function and urine creatinine level (p>0,05).